Whole genomic sequence analysis of Bacillus infantis: defining the genetic blueprint of strain NRRL B-14911, an emerging cardiopathogenic microbe. (August 2016) - Massilamany, Chandirasegaran; Mohammed, Akram; Loy, John; Purvis, Tanya; Krishnan, Bharathi; Basavalingappa, Rakesh; Kelley, Christy; Guda, Chittibabu; Barletta, Raúl; Moriyama, Etsuko; Smith, Timothy; Reddy, Jay
Abstract Background We recently reported the identification ofBacillus sp. NRRL B-14911 that induces heart autoimmunity by generating cardiac-reactive T cells through molecular mimicry. This marine bacterium was originally isolated from the Gulf of Mexico, but no associations with human diseases were reported. Therefore, to characterize its biological and medical significance, we sought to determine and analyze the complete genome sequence ofBacillus sp. NRRL B-14911. Results Based on the phylogenetic analysis of 16S ribosomal RNA (rRNA) genes, sequence analysis of the 16S-23S rDNA intergenic transcribed spacers, phenotypic microarray, and matrix-assisted laser desorption ionization time-of-flight mass spectrometry, we propose that this organism belongs to the speciesBacillus infantis, previously shown to be associated with sepsis in a newborn child. Analysis of the complete genome ofBacillus sp. NRRL B-14911 revealed several virulence factors including adhesins, invasins, colonization factors, siderophores and transporters. Likewise, the bacterial genome encodes a wide range of methyl transferases, transporters, enzymatic and biochemical pathways, and insertion sequence elements that are distinct from other closely related bacilli. Conclusions The complete genome sequence ofBacillus sp. NRRL B-14911 provided in this study may facilitate genetic manipulations to assess gene functions associated with bacterial survival and virulence. Additionally, this bacterium may serve as a useful tool to establish a disease model that permits systematic analysis of autoimmune events in various susceptible rodent strains.